Penggunaan Televisi Lokal Sebagai Media Pembelajaran Jarak Jauh Sekolah Dasar Kota Cirebon - Nadia Jamali; Budi Puspo Priyadi; Endang Larasati; Ida Hayu Dwimawanti; Teuku Afrizal (PERSPEKTIF, 2022)
Covid-19 has an impact on the education sector so that it experiences a distance learning process. The purpose of this study was to find out how to use distance learning media, with a research locus in Karya Mulya 1 Elementary School Cirebon City. This study uses distance learning theory by Keegan (2011). Sources of data obtained from documentation, observation, direct interviews or by telephone with 24 informants. The results of the study found that Karya Mulya 1 Elementary School in the use of distance learning media had obstacles experienced by teachers and students. The Cirebon City Education Office made a Learning From Home policy which was carried out through offline (using RCTV media) and online (using Whatsapp Group applications) approaches simultaneously. The suggestions given include: evaluating the policy of the home learning program through RCTV, holding regular training workshops on technology for SD Karya Mulya 1 teachers, Cirebon City Government collaborating with providers to provide learning quota assistance, and providing information on learning tool assistance long distance to parents of students.